2017
DOI: 10.3389/fpubh.2017.00328
|View full text |Cite
|
Sign up to set email alerts
|

Are Exposures to Multiple Frequencies the Key to Future Radiofrequency Research?

Abstract: There is an extensive literature investigating possible effects of exposure to radiofrequency (RF) electromagnetic fields associated with mobile phone technologies. This has not identified any public health risks with any degree of certainty. Some epidemiological studies have observed associations between heavy users of mobile phones and some types of cancer, but animal studies do not support this association, although a few studies have reported increased tumor yields. However, there is a crucial difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
0
13
0
2
Order By: Relevance
“…Действительно, в 1980-1990-е годы сообщалось о повышении риска лейкозов у детей, проживавших вблизи линий электропередач. Как обсуждалось выше, эпидемиологические данные в пользу канцерогенного эффекта ЭМИ РЧ могли быть обусловлены систематической ошибкой и мешающими факторами; убедительных экспериментальных подтверждений получено не было, действие тех или иных физиологических механизмов не доказано [35,36,45,47,58,[70][71][72]74].…”
Section: Discussionunclassified
“…Действительно, в 1980-1990-е годы сообщалось о повышении риска лейкозов у детей, проживавших вблизи линий электропередач. Как обсуждалось выше, эпидемиологические данные в пользу канцерогенного эффекта ЭМИ РЧ могли быть обусловлены систематической ошибкой и мешающими факторами; убедительных экспериментальных подтверждений получено не было, действие тех или иных физиологических механизмов не доказано [35,36,45,47,58,[70][71][72]74].…”
Section: Discussionunclassified
“…Long-term exposures to EMF have consistently shown no increase in cancer risk in animal experiments [48,54,55]. Numerous in vitro studies have been negative as well, while the more research quality criteria were satisfied, the less cellular responses tended to be observed [56,57].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Although both the incidence of certain types of brain cancers (Khurana et al, 2009, de Vocht et al, 2011, Zada et al, 2012, Yang et al, 2017 and use of mobile phones (and other wireless technology) (Khurana et al, 2009) have been increasing over the last 2 decades, and despite extensive research it remains unclear whether this is a question of causation or correlation (Sienkiewicz et al, 2017). Based on all available evidence at the time, The International Agency for Research on Cancer (IARC) concluded in 2011 that exposure to radiofrequency radiation (RF) in the frequency range 30 kHz to 300 GHz, which includes the frequencies used by mobile phones (Cardis et al, 2011), should be classified as 2B (possibly carcinogenic to humans) taking into account positive associations between glioma and acoustic neuroma, and exposure to RF-EMF from wireless phones (Baan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Based on all available evidence at the time, The International Agency for Research on Cancer (IARC) concluded in 2011 that exposure to radiofrequency radiation (RF) in the frequency range 30 kHz to 300 GHz, which includes the frequencies used by mobile phones (Cardis et al, 2011), should be classified as 2B (possibly carcinogenic to humans) taking into account positive associations between glioma and acoustic neuroma, and exposure to RF-EMF from wireless phones (Baan et al, 2011). Results from the National Toxicology Program (NTP) in rats seem to support this, with results suggesting an increased incidence of malignant glioma, as well as schwannomas of the heart in male, but not female, rats after whole-body averaged Specific Absorption Rate (SAR) levels that were comparable to the maximum localised SAR levels occurring in human head tissues located near to a mobile phone during a call (Wyde et al, 2016, NTP, 2018a, NTP, 2018b; however, there are some queries about these results, including their comparison with human exposures, and the study is yet to be published in peer-reviewed literature (Sienkiewicz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation